(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the role of personalized learning in enhancing the quality and effectiveness of modern education. It highlights the importance of individualized educational approaches that consider each student’s unique needs, interests, and abilities to foster professional motivation and long-term engagement. The author emphasizes the integration of digital technologies to create flexible, adaptive learning paths and self-directed educational environments. A central focus is the development of platforms and tools that support learner autonomy, reflective self-assessment, and collaboration with mentors. Ultimately, the article advocates for a paradigm shift toward a student-centered model that prioritizes personal development, innovation, and lifelong learning.